Precision targeting of right dorsolateral prefrontal cortex with neuronavigated rTMS alleviates chronic insomnia via functional connectivity reorganization: a randomized neuroimaging trial - Liang Gong; Xi Yang; Yuan He; Haoyu Li; Wen Zhou; Duan Liu; Bei Zhang; Chunhua Xi (NeuroImage: Clinical)
Background: Repetitive transcranial magnetic stimulation (rTMS) offers a promising approach for the treatment of insomnia; however, the precise targets and underlying neural mechanisms remain unclear. This randomized, wait-controlled trial aimed to evaluate the clinical efficacy of neuronavigated rTMS targeting the right dorsolateral prefrontal cortex (DLPFC) in chronic insomnia disorder (CID) and to identify potential neural mechanisms associated with therapeutic outcomes. Methods: Fifty patients with CID were randomized to receive 20 sessions of 1 Hz rTMS targeting the right DLPFC or to a waitlist control group. Stimulation coordinates were selected (MNI: 40,39,11) based on our previous neuroimaging meta-analysis, and were precisely localized using MRI-guided neuronavigation. Clinical assessments and resting-state fMRI were conducted before and after the intervention, respectively. Target-based functional connectivity (FC) analysis was used to map rTMS-associated network changes, while causal mediation analysis was used to examine the relationships between neural changes and clinical improvements. Results: Compared to waitlist controls, the rTMS group showed greater improvements in insomnia and mood symptoms (all p < 0.001), with higher response rates (54.55 % vs. 9.09 %) and remission rates (68.18 % vs. 13.64 %). FC analysis showed significant group × time effects on the bilateral DLPFC, middle cingulate cortex, and right anterior cerebellar vermis. Mediation analysis indicated that FC changes in the right DLPFC mediated 24 % of the improvement in insomnia severity (Insomnia Severity Index, p = 0.048). Conclusion: These preliminary findings suggest that precision neuronavigated rTMS targeting the right DLPFC may alleviate insomnia symptoms, with the observed clinical improvements potentially related to the reorganization of the DLPFC network. While these results are encouraging, further research based on placebo-controlled study designs is required to confirm these effects and better understand the underlying mechanisms. This study provides preliminary evidence supporting the integration of precision targeting with neuroimaging to explore the mechanisms underlying the effects of rTMS in insomnia treatment.